Fixing the hole in the bucket: household poverty dynamics in the Peruvian Andes - Krishna, A.; Kristjanson, Patricia M.; Radeny, Maren A.O.; Kuan, J.; Quilca, G.; Sánchez Urrelo, A. (Wiley, 2006)
Achieving the Millennium Development Goal of halving poverty will require simultaneous action on two separate fronts: helping poor people escape from poverty, and stemming the flow of people into poverty. This article examines forty Peruvian communities, and finds that descents into poverty have occurred alongside escapes in every one of them. Escape and descent are asymmetric in terms of reasons: while one set of reasons is responsible for escapes from poverty, another and different set of reasons is associated with descent. Making progress in poverty reduction will require measures to accelerate escapes whilst at the same time slowing down descents. The article looks at the different policies which will be required to serve these two separate purposes.